Construction and models of multicultural competences - Jakub Hladík (Pedagogická Orientace, 2010)
The paper is focused on multicultural competences which are an importantpart of multicultural education. The author focuses on multicultural competences de-finition and development, and then on selected models of multicultural competences.Models of multicultural competences (Hierarchical, Pyramid, AKS, ICC and Process) areanalyzed in the light of their construction and construct elements. The aim of this paperis to provide a basic presentation of multicultural competences’ models, accomplishtheir basic classification and show some differences between the above mentionedmodels.